Francis turbine high load instabilities – Model test and CFD simulation. Issue 2 (March 2019) - Rodriguez, D; Rivetti, A; Angulo, M; Lucino, C; Liscia, S
Abstract: When operating under high load conditions, Francis turbines tend to develop a typical central vortex located under the runner cone. Usually, this central vortex has an axisymmetric main part with helicoidal tail. Under cavitating conditions, this central vapor cavity may become unstable, generating synchronic pressure pulsations (known as self-excited oscillations) which propagate into the entire machine. The volume of the vapor cavity is a relevant feature as it influences the frequency of these pressure pulsations. Numerical flow simulations together with model test measurements and visualizations allow the characterization of the high load vortex pattern developed under different operating and Sigma plant conditions. In this work, model tests and transient two-phase CFD simulations were carried out for a medium-head Francis model scale operating under high load conditions. The vortex instability zone measured and numerical simulated on model scale is presented.